Canada and transboundary fisheries management in changing oceans: taking stock, future scenarios - U. R. Sumaila (Resilience Alliance, 2020)
This article is the Introduction to the Special Feature entitled: Canada and Transboundary Fisheries Management in Changing Oceans: Taking Stock, Future Scenarios. We summarize the research context of the four papers in the Special Feature.